Mathematics A: For Students of FKKT UM - Žigert Pleteršek, Petra; Črepnjak, Matevž (University of Maribor Press, 2022)
Mathematics A: For Students of FKKT UM The higher education textbook represents an introduction to mathematical analysis at the faculties of natural sciences and technology. In addition to the basic concepts of sets, logic, and numbers, real functions and the related concepts of function limits and continuity, as well as sequences and series, are discussed. The contents of the differential calculus with the application to the use of the derivative of a function, and the integral part of calculus are also covered.